Successful Treatment of Early Relapsed High-Risk AML After Allogeneic Hematopoietic Stem Cell Transplantation With Biomodulatory Therapy - Kattner, Anna-Sophia; Holler, Ernst; Herr, Wolfgang; Reichle, Albrecht; Wolff, Daniel; Heudobler, Daniel (Frontiers in Oncology, 2020)
Early relapse of acute myeloid leukemia (AML) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains a therapeutic challenge that is often unsuccessful. Established therapy regimens include hypomethylating agents (HMA), discontinuation of immunosuppression (IS) and donor lymphocyte infusion (DLI) as early preemptive treatment options or after diagnosis of molecular recurrence of disease. In cases of hematologic relapse, chemotherapy and DLI are therapeutic options. Since treatment options are few and many fail, new approaches such as de novo allo-HSCT (mostly in late relapse situation), targeted therapies and biomodulatory drugs have evolved (Zeiser et al., 2019). Despite these options, prognosis is very poor. In this manuscript we present an unusual case of a patient with high risk acute myeloid leukemia (AML) with an unbalanced jumping translocation and FLT3-TKD low mutation who presented with early relapse (FLT3 negative) after allo-HSCT refractory to one cycle of azacitidine as well as discontinuation of IS. As salvage therapy, the patient received a biomodulatory therapy consisting of low-dose azacitidine 75 mg/day (given s.c. d1-7 of 28), pioglitazone 45 mg/day orally, and all-trans-retinoic acid (ATRA) 45 mg/m2/day orally. The patient showed absence of leukemia in the peripheral blood after one and complete remission in the bone marrow after two cycles of therapy. Even after cessation of treatment after 5 cycles of therapy, the patient remained in complete remission with full chimerism in peripheral blood and bone marrow for another 7 months. In conclusion, we report about an unusual case of long-lasting complete remission of early relapsed high-risk AML after allo-HSCT treated with azacitidine, pioglitazone and ATRA after failure of standard of care treatment with HMA and discontinuation of IS.